![f ( x ) = \sqrt{ x^{4} -16 x^{2} }](https://tex.z-dn.net/?f=f%20%28%20x%20%29%20%3D%20%20%5Csqrt%7B%20x%5E%7B4%7D%20-16%20x%5E%7B2%7D%20%7D%20)
a ) The domain:
x^4 - 16 x² ≥ 0
x² ( x² - 16 ) ≥ 0
x² - 16 ≥ 0
x² ≥ 16
x ∈ ( - ∞, - 4 ] ∪ [ 4 , + ∞ )b ) f ` ( x ) =
![\frac{1}{2 \sqrt{x ^{4}-16 x^{2} } } * ( x^{4}-16 x^{2} )` =](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%20%5Csqrt%7Bx%20%5E%7B4%7D-16%20x%5E%7B2%7D%20%20%7D%20%7D%20%2A%20%20%28%20x%5E%7B4%7D-16%20x%5E%7B2%7D%20%29%60%20%3D%20)
=
( 2 x³ - 16 x ) / √(x^4 - 16 x²)c ) The slope of the tangent line at x = 5:
f ` ( 5 ) = ( 2 * 125 - 16 * 5 ) / √ ( 625 - 400 ) = 170 / 15 = 34 / 3
The slope of the line normal to the graph at x = 5:
m = - 3 / 34
Answer:
7,7, and 7
Step-by-step explanation:
If she vase is cubical we know that all 3 dimensions are the same. This means that x^3 = 343. So we know the answer is the cube root of 343, which is 7
The length of a curve <em>C</em> parameterized by a vector function <em>r</em><em>(t)</em> = <em>x(t)</em> i + <em>y(t)</em> j over an interval <em>a</em> ≤ <em>t</em> ≤ <em>b</em> is
![\displaystyle\int_C\mathrm ds = \int_a^b \sqrt{\left(\frac{\mathrm dx}{\mathrm dt}\right)^2+\left(\frac{\mathrm dy}{\mathrm dt}\right)^2} \,\mathrm dt](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint_C%5Cmathrm%20ds%20%3D%20%5Cint_a%5Eb%20%5Csqrt%7B%5Cleft%28%5Cfrac%7B%5Cmathrm%20dx%7D%7B%5Cmathrm%20dt%7D%5Cright%29%5E2%2B%5Cleft%28%5Cfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dt%7D%5Cright%29%5E2%7D%20%5C%2C%5Cmathrm%20dt)
In this case, we have
<em>x(t)</em> = exp(<em>t</em> ) + exp(-<em>t</em> ) ==> d<em>x</em>/d<em>t</em> = exp(<em>t</em> ) - exp(-<em>t</em> )
<em>y(t)</em> = 5 - 2<em>t</em> ==> d<em>y</em>/d<em>t</em> = -2
and [<em>a</em>, <em>b</em>] = [0, 2]. The length of the curve is then
![\displaystyle\int_0^2 \sqrt{\left(e^t-e^{-t}\right)^2+(-2)^2} \,\mathrm dt = \int_0^2 \sqrt{e^{2t}-2+e^{-2t}+4}\,\mathrm dt](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint_0%5E2%20%5Csqrt%7B%5Cleft%28e%5Et-e%5E%7B-t%7D%5Cright%29%5E2%2B%28-2%29%5E2%7D%20%5C%2C%5Cmathrm%20dt%20%3D%20%5Cint_0%5E2%20%5Csqrt%7Be%5E%7B2t%7D-2%2Be%5E%7B-2t%7D%2B4%7D%5C%2C%5Cmathrm%20dt)
![=\displaystyle\int_0^2 \sqrt{e^{2t}+2+e^{-2t}} \,\mathrm dt](https://tex.z-dn.net/?f=%3D%5Cdisplaystyle%5Cint_0%5E2%20%5Csqrt%7Be%5E%7B2t%7D%2B2%2Be%5E%7B-2t%7D%7D%20%5C%2C%5Cmathrm%20dt)
![=\displaystyle\int_0^2\sqrt{\left(e^t+e^{-t}\right)^2} \,\mathrm dt](https://tex.z-dn.net/?f=%3D%5Cdisplaystyle%5Cint_0%5E2%5Csqrt%7B%5Cleft%28e%5Et%2Be%5E%7B-t%7D%5Cright%29%5E2%7D%20%5C%2C%5Cmathrm%20dt)
![=\displaystyle\int_0^2\left(e^t+e^{-t}\right)\,\mathrm dt](https://tex.z-dn.net/?f=%3D%5Cdisplaystyle%5Cint_0%5E2%5Cleft%28e%5Et%2Be%5E%7B-t%7D%5Cright%29%5C%2C%5Cmathrm%20dt)
![=\left(e^t-e^{-t}\right)\bigg|_0^2 = \left(e^2-e^{-2}\right)-\left(e^0-e^{-0}\right) = \boxed{e^2-\frac1{e^2}}](https://tex.z-dn.net/?f=%3D%5Cleft%28e%5Et-e%5E%7B-t%7D%5Cright%29%5Cbigg%7C_0%5E2%20%3D%20%5Cleft%28e%5E2-e%5E%7B-2%7D%5Cright%29-%5Cleft%28e%5E0-e%5E%7B-0%7D%5Cright%29%20%3D%20%5Cboxed%7Be%5E2-%5Cfrac1%7Be%5E2%7D%7D)
Answer:
12
Step-by-step explanation:
Answer:
4
Step-by-step explanation: